GROWTH ANALYSIS OF CHINESE LIQUOR LISTED COMPANIES BASED ON PRINCIPAL COMPONENT ANALYSIS - Jun Luo; Xiaoyu Shi; Jingwei Liu (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
Online shopping has been increasingly popular in recent years due to the spread of the Internet, and the livestream sector has increased. Many traditional companies, such as Chinese liquor enterprises, tried to engage in livestreaming to keep pace with their new customers. The overall perceived value’s impact on user behavior has been examined in social commerce research, but the livestream context has received less attention. This study proposed and empirically tested a theoretical model, considering online word-of-mouth, and investigated the effect of consumer perceived value on livestream purchase intention of Chinese liquor. The findings demonstrate that online word-of-mouth serves as a mediator between the three dimensions of perceived value - functional, emotional, and social value - and livestream purchase intentions of Chinese liquor.